Аналіз витрат населення - Яковенко, Р. В.; Yakovenko, R. (My University, 2018)
Стаття аналізує структуру витрат населення, потенційну місткість споживчого ринку та показники рівня розвитку окремих галузей національної економіки. The article analyzes the structure of population spending, the potential capacity of the consumer market and indicators of the level of development of separate branches of the national economy.
Population expenditure analysis
Keywords: витрати; кінцеве споживання; місткість споживчого ринку; показники рівня розвитку галузей; costs; final consumption; capacity of the consumer market; indicators of the level of development of branches